Raman spectroscopy for agricultural applications - Juárez, Isaac D.; Kurouski, Dmitry (Frontiers in Plant Science, 2025)
Over the last decade, we observe a significant interest in Raman spectroscopy expressed by plant biologists and other agriculturalists. However, many of these people have limited experience in Raman analyses. To this end, we wrote an extensive method-focused manuscript in which we critically discuss key steps in analyses for spectroscopic data. We also conveyed the major differences between analysis of certain peaks vs the full spectra, as well as discussed how both types of spectral analyses could complement each other. We also focused on chemometric analysis of data, including supervised methods, such as PLS-DA. Using our own data, we demonstrated a contribution of spectral preprocessing, model parameters and validation in the performance of supervised methods in data classification. We also critically discussed practical applications of peak fitting and 2-D correlation spectroscopy and demonstrated how these approaches can be useful to extract valuable information about biological processes that take place in plants.